Reading and Learning Smartfonts - Bragg, Danielle; Azenkot, Shiri; Kalai, Adam Tauman (UIST '16 Proceedings of the 29th Annual Symposium on User Interface Software and Technology, 2016)
As small displays on devices like smartwatches become increasingly common, many people have difficulty reading the text on these displays. Vision conditions like presbyopia that result in blurry near vision make reading small text particularly hard. We design multiple different scripts for displaying English text, legible at small sizes even when blurry, for small screens such as smartphones and smartwatches. These "smartfonts" redesign visual character presentations to improve the reading experience. Like cursive, Grade 1 Braille, and ordinary fonts, they preserve orthography and spelling. They have the potential to enable people to read more text comfortably on small screens, e.g., without reading glasses. To simulate presbyopia, we blur images and evaluate their legibility using paid crowdsourcing. We also evaluate the difficulty of learning to read smartfonts and observe a learnability/legibility trade-off. Our most learnable smartfont can be read at roughly half the speed of Latin after two thousand practice sentences. It is also legible smaller than half the size of traditional Latin (i.e. "English") when blurry.